Post-COVID-19 conditions and health effects in Africa: a scoping review - Mustapha Amoadu; Promise Kwame Salu; David N Banaaleh; Edward W Ansah; Martin S Daanko (BMJ Open)
Introduction The SARS-CoV-2 pandemic has caused global devastations in social, economic and health systems of every nation, but disproportionately of nations in Africa. In addition to its grave effects on the global systems, there is continuation or development of new symptoms among individuals who have contracted the virus, with the potential to further stress the health systems on the continent. Therefore, the aim of this scoping review was to collate and summarise the existing research evidence on the prevalence and health effects of post–COVID-19 conditions in Africa.Methods and analysis Five main databases were thoroughly searched from 1 September 2023 to 10 May 2024 for eligible articles based on the pre-established inclusion and exclusion criteria. These databases included PubMed, Central, Scopus, Dimensions AI and JSTOR. A total of 17 papers were included in the review. The protocol for this review is already published in BMJ Open; doi:10.1136/bmjopen-2023-082519.Results The prevalence of post–COVID-19 conditions in Africa ranged from 2% to as high as 94.7%. Fatigue, dyspnoea and brain fog were among the commonly reported symptoms of post–COVID-19 conditions. Reduced functional status as well as physical and psychosocial disorders were the main health effects reported by the studies reviewed, but no study yet reported the effects of post–COVID-19 conditions on the health systems in Africa.Conclusions There is an evidence of high prevalence of post–COVID-19 conditions in the African setting. However, there is limited evidence of the health effects of the post–COVID-19 conditions on patients and health systems in Africa.Ethics and dissemination This scoping review involved analysis of secondary data; therefore, no ethical approval was needed. Dissemination of the result is being done through international journals and may also be presented at available research conferences.